Electric Quadrupole Radiation Strength in Neutron Capture - Islam, Aminul M. (My University, 1982)
A high resolution NaI(Tl) -Ge pair spectrometer has been used to detect the primary E2 transitions following thermal neutron capture in ¹⁴³Nd, ¹⁶²Dy, ¹⁶⁴Dy, ¹⁶⁵Ho, ¹⁶⁷Er, ¹⁷³Yb and ¹⁷⁹Hf. These data, as well as other thermal, resonance and average-resonance data have been analyzed to study the radiative quadrupole strength. Some calculations have been done to retrieve the E2 intensities from the average-resonance work. A quantitative theoretical expression for the quadrupole strength function on the basis of the giant quadrupole resonance model is deduced. A comparison between the experimental and theoretical values for nuclei spanning the mass region between A=12 to A=239 shows the presence of the influence of the GQR on the radiation strength. A depression in the quadrupole strength has been observed in the mass range 144
The energy and intensity of all the observed high energy transitions in most of the nuclei under study are presented. A set of neutron separation energies of 15 isotopes of Nd, Gd, Dy, Ho, Er, Yb and Hf has been estimated. The thermal radiative capture cross section of ¹⁴N, a standard used in this work, is determined with improved precision.
Keywords: Physics; Physics